News: Adam Kay: Stories From A Former Medic - Garami, Anna (Trinity Student Medical Journal, 2018)
This past Monday, the Robert Smith Lecture Theatre in Saint James’s Hospital filled up —except for the front row, presumably a universal law for any given lecture theatre — for a lunchtime talk with Adam Kay. The former senior registrar in obstetrics and gynaecology, and author of the bestseller This Is Going to Hurt, spoke about his book based on the diaries he kept throughout his years working in the NHS. Trinity College’s BioSoc hosted the now-TV writer/comedian and awarded him an honorary patronage of the society on the same day as his sold out gig at the National Concert Hall in Dublin. The audience of about 200 was made up largely of medical students, but a good few junior doctors were attending as well — bleeps going off at regular intervals provided a subtle but apropos background for the talk. The event began by awarding the medal to Kay, followed by a reading of a passage from the book (one of two genital-degloving anecdotes the audience was treated to in the short space of an hour) and a conversation with Rían Hayes, president of BioSoc, who made sure to crush any smidgen of doubt as to whether he had “done his research” for the event. In fairness to him, this did show, and resulted in a nicely flowing and informative conversation. The last part involved the audience in a Q&A session with the comedian. Kay’s delivery of anecdotes and sarcastic remarks were honoured with a good chuckle each time without fail. In response to a question about whether he had additional funny stories that didn’t make the final cut — he answered with degloving story number two which elicited the same cringe-eliciting response as the first. He went further to compare his work on the book to that of a sound mixer, trying to find the right balance between funny, serious, absurd and tragic, and he made sure his audience got a taste of all sides during his talk. For every story about hungover students ending up face-first in a patient’s abdomen, he also gave glimpses into a life where six out of seven missed Christmases was the norm. An amusing recount of a meeting with British Politician Jeremy Hunt (who more than likely agreed to the meeting to stop the constant stream of Kay’s book addressed to him flooding his office) displayed how the issue of burnout is ever-increasing in the medical profession. My very first thought after finishing the book (in a single afternoon, which is testament to how entertaining the writing is) was that I should buy this for friends and family, as it conveys the nature of my future occupation more accurately (and probably in an infinitely more entertaining manner) than any of my recounts of personal experiences. Kay confirmed that this was no accident. “I wanted it to be the books that doctors could say: This is what it’s like!” he said, proving not only that he had very clear intentions with publishing his story, but that the execution was spot-on. Another message that was obviously important to the author, and one that his story very much underlines, is the necessity of healthcare professionals taking good care of themselves and each other. He stressed how vital it is to be armed with some personal way of coping in such a challenging line of work. One audience member intending to work in the UK inquired about whether things have improved since he left his job in the NHS. Kay gave a sobering reminder of further cuts to the health care budget after 2010 and did no sugarcoating in pointing out how the ultimate solution would be “loads of more money.” He said that objectively, individuals, or even doctors as a group, could do very little to change things in that regard. On a more positive note, Kay also pressed the importance of making a decision on a career path with “both eyes wide open”, musing on how this crucial choice in his case may have been influenced during medical school by a well-respected registrar. Kay compared different specialties to being like sine waves, some — such as O&G — with extreme highs and lows, and others with somewhat flatter waveforms (insert obvious jab at dermatology), something he strongly advised to take into account when choosing a career. When the conversation turned to his life as a comedian and TV-writer, Kay didn’t shy away from getting very real about how different the satisfaction that his current job and that being a doctor provided, describing the former as being a lot less tangible and several degrees removed from the impact it was making. This was one of the few times during the talk when some sense of remorse seeped through his words. The same could be felt when he was talking about the end of his days as a doctor, and how hard he found it to open up about what he was going through at the time. As a member of the audience put it afterwards: “Despite how funny he was, you could still sense the sadness he felt around the events that ended his career.” While many of the answers were based largely on the book, with a good few almost direct quotes from diary entries, Kay’s deadpan delivery kept even those who could see the punchline coming very much entertained. The audience also heard several unwritten stories, for instance painting the hilarious picture of the comedian performing (after a kindly warm-up from Ellie Goulding) a foul-mouthed parody song about the London Underground at Prince Harry’s birthday in St James’s Palace. Just as reading his book, this talk with Adam Kay was thoroughly entertaining, if somewhat bittersweet. It’s no surprise whatsoever that he seemed to have struck a chord with the crowd in the lecture theatre of a university hospital: his honesty, down to earth personality, and sarcastic humour gave his very important messages about doctors’ well being, or the state of health care a rare degree of authenticity. Apart from heartfelt giggles about the absurdity of what medicine can be at times, Kay’s story and current work also encourage to take the time to make well thought out decisions in pursuing this demanding career. Given the flying start of his new career, and the amount of people he reached one way or another in the last few years, I do believe there is genuine hope for maybe a couple less “guns and badges” handed in before their time down the line – and quite possibly a surge in secret diary-keeping among junior doctors. Photographs Courtesy Joe Deegan